Hubungan Masa Kerja Dan Usia Kerja Dengan Kelelahan Fisik Pada Pekerja Wanita - Nina Fentiana; Daniel Ginting (Lembaga Pengembangan Kinerja Dosen, 2023)
Every year two million female teachers fall victim to work-related injuries due to fatigue. A National Safety Council study of 2,010 US female teachers found that burnout was responsible for about 13% of workplace accidents. The aim of this study was to look at the relationship between length of work and working age with physical fatigue in female workers who work as elementary school teachers. The study used a cross-sectional approach that collected data on private elementary school teachers in the City of Penyabungan, Mandailing Natal Regency, North Sumatra. The results of the study concluded that there is a relationship between length of work and workload with work fatigue in female workers. So it takes time to rest and stretch on the sidelines of work to avoid excessive physical fatigue.